2017
DOI: 10.1097/wnf.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Schizophrenia Associated With Obsessive-Compulsive Disorder: Clinical Features and Correlates

Abstract: Adolescents with schizophrenia and OCD needed more antipsychotic doses for acute exacerbation and the maintenance of reduction of psychosis severity than adolescents with only schizophrenia. We could suggest that OCD comorbidity in schizophrenia is more treatment resistant, although the severity of the schizophrenia was similar between study groups. There was no correlation between OCD and schizophrenia symptoms either.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…The higher treatment doses of clozapine in the OCD group replicates previous findings (Baytunca et al, 2017, Fernandez-Egea et al, 2018) and remained consistent in confirmatory multilinear regression analysis. This could have various explanations such as biological sex, where males require higher doses, and smoking status, where smokers require higher doses.…”
Section: Discussionsupporting
confidence: 88%
“…The higher treatment doses of clozapine in the OCD group replicates previous findings (Baytunca et al, 2017, Fernandez-Egea et al, 2018) and remained consistent in confirmatory multilinear regression analysis. This could have various explanations such as biological sex, where males require higher doses, and smoking status, where smokers require higher doses.…”
Section: Discussionsupporting
confidence: 88%
“…The change in insight in delusions has not been systematically investigated. Given the variability of insight between obsessions and delusions, it is understood that insight does not constitute a reliable basis for discrimination (Sa et al, 2009) Some authors suggested that the coexistence of schizophrenia and OCD reflects a different psychopathology and suggested the definition of schizo-obsessive subtype to this different group (Baytunca et al, 2017;Kazhungil et al, 2017;Meier et al, 2014). Poyurovsky et al (2004) defined the spectrum of schizoobsession, and stated that the concept of obsessive psychosis would be appropriate for patients with coexistence.…”
mentioning
confidence: 99%
“…Some researchers have suggested that the presence of some overlapping symptoms in OCD and schizophrenia may be due to the similarities in neurological circuits, anatomical structures, and neurotransmitters shown for each disorder (Baek et al, 2020). Reports of psychotic-themed obsessions in schizophrenic patients further complicate the clinical distinction (Baytunca et al, 2017).…”
mentioning
confidence: 99%
“…Comorbid schizophrenia-OCD (schizo-OCD) is characterized by the concurrent presentation of psychotic and obsessive-compulsive symptoms (86,(88)(89)(90), that may require high antipsychotic dosages for its acute exacerbations and for the maintenance of reduction of the severity of psychosis (91). Schizo-OCD sufferers show a distinct ERP pattern, with abnormally increased target activation similar to that described in OCD (20) but different from that usually observed in schizophrenia (76).…”
Section: P300 In Ocd Overlapping With Other Disordersmentioning
confidence: 99%